The future remembered : the 1962 Seattle world's fair and its legacy - Becker, Paula (Seattle Center Foundation, 2011)
This is the history of the 1962 World's Fair in Seattle, Washington. It also covers the 50 years after the fair and how Seattle has used the site to continue the dream of the original World's Fair by turning it into a civic and cultural hub that continues to grow and evolve with the changing city. One such addition is the Experience Music Project.